The Extent of Tributary Incision in Response to Knickpoint Migration on the Lower Chippewa River in West-Central Wisconsin - Hilgendorf, Zach (My University, 2015)
The Lower Chippewa River (LCR) is a tributary to the Upper Mississippi River (UMR) in west-central Wisconsin. Its valley contains several terraces resulting from the apparent episodic upstream migration of knickpoints initiated by UMR incision during Late Wisconsinan deglaciation. We investigated tributaries to the LCR to determine if they reflect this apparent episodic knickpoint migration. First, we interpreted digital elevation models to establish the upstream extent of incision on tributary networks, verifying our interpretations with field checks. Then, using ArcMap, we quantified incision extent for each tributary network by summing the lengths of stream polylines from tributary mouth to the upstream points of incision. A plot of incision extent (normalized by tributary drainage area) against distance from the Mississippi indicates tributaries closest to the Mississippi are more extensively incised. It also reveals a sharp decline in tributary incision upstream from the Red Cedar River (RCR), the largest tributary of the LCR. This suggests that RCR incision, itself initiated by LCR incision, produced a large influx of sediment to the LCR, temporarily halting the LCR knickpoint.
Color poster with text, photographs, maps, and graphs.
Keywords: River migration; Tributaries; Lower Chippewa River (LCR); Posters